2013
DOI: 10.1002/ppsc.201200137
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Directed Gold Microwires by Self‐Organization of Nanoparticles on Aspergillus Niger

Abstract: A directional point‐to‐point growth of microwires of gold nanoparticles (AuNPs) self‐organized on Aspergillus niger (A. niger) templates by utilizing positive phototropic fungal response to different spectral ranges of visible light is reported. A. niger serves as a living template for the self‐organization of monosodium glutamate (MSG) capped gold colloids under controlled nutrient trigger and appropriate light, temperature, and humidity conditions. The experimental results show that control of these paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In present paper we outline our scoping experimental results on evaluating properties of protoplasmic tubes as electrical wires. Our finding discussed in the paper complement previous studies on fabrication of organic wires and using living substrates to grow metallised conductive pathways: self-assembling molecular wires [54,44], DNA wires [16], electron transfer pathways in biological systems [32], live bacteria templates for conductive pathways [17], bio-wires with cardiac tissues [18], golden wires with templates of fungi [45].…”
Section: Introductionsupporting
confidence: 82%
“…In present paper we outline our scoping experimental results on evaluating properties of protoplasmic tubes as electrical wires. Our finding discussed in the paper complement previous studies on fabrication of organic wires and using living substrates to grow metallised conductive pathways: self-assembling molecular wires [54,44], DNA wires [16], electron transfer pathways in biological systems [32], live bacteria templates for conductive pathways [17], bio-wires with cardiac tissues [18], golden wires with templates of fungi [45].…”
Section: Introductionsupporting
confidence: 82%
“…It is possible that subsequent multilayers were formed due to the entropic contribution while the Brownian motion was responsible for the nanoparticles migration from the medium to the hyphae surface. 22 However, these successive layers cannot be simply explained in terms of chemical bonds between nanoparticles and the fungus. Therefore, some attractive interaction should occur between these nanoparticles mediated by molecules secreted by the fungus [23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] Heterostructures consisting of multilayers with controlled thickness have been constructed owing to interactions between nanoparticles and biotemplates. 16,17 Particularly, fungi can be effectively used as biotemplates since they are skilled at adapting in distinct environments. This versatility extends to their peculiar shapes, ranging from mushrooms to microfilaments.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, improvement of acid protease production was found in the mixed culture of A. niger and A. oryzae using solid-state fermentation ( 32 ). Studies have also shown that A. niger has a positive photogenic response to white light ( 33 ), and the production of conidia and glucoamylase was promoted by continuous illumination with blue light ( 34 ). Considering blue light inhibited the mycelial growth and conidiation of A. oryzae GDMCC 3.31, blue light can be used to regulate the koji of a mixed strain of A. oryzae and A. niger .…”
Section: Discussionmentioning
confidence: 99%